Is the Thoughts and Health programme feasible in the context of Swedish schools? A quasi-experimental controlled trial study protocol. Issue 1 (22nd January 2021) - Wikberg, Carl; Augustsson, Pia; Sveinsdottir, Gudny; Craighead, W Edward; Arnarson, Erikur Örn; Marteinsdottir, Ina; Lilja, Josefine L
Abstract : Introduction: Clinical depression is a substantial problem among adolescents, increasing significantly at about age 15 years. It causes impairment in social, academic and familial relationships, as well as ongoing cognitive and emotional difficulties for the individual. A study in Iceland demonstrated that a cognitive–behavioural, developmentally based intervention programme, 'Thoughts and Health', prevented initial episodes of depression and/or dysthymia (DYS) (major depressive disorder/DYS) in adolescents for up to 12 months following completion of the programme. We would like to test the feasibility of implementing the Icelandic method in a Swedish context and to evaluate the long-term effects of such a programme. Methods and analysis: A quasi-experimental controlled design, combined with qualitative and quantitative methods, will be used to address the research questions. In this study, 617 children aged ~14 years will be screened for depression, and those "at risk" for development of clinical depression will be offered a 12 week course, 'Thoughts and Health'. This course aims to prevent first depression in adolescents. A comparable group of children will function as controls. Depending on the type of variable, baseline comparisons between the two groups of relevant initial measures will be evaluated with t-tests or χ 2 analyses. The effects of the programme on the development of clinical levels of depression will be evaluated using the follow-up data of 6, 12 and 18 months. Index parental depression at baseline will be tested as a moderator in the evaluation of the effects of the prevention programme. Ethics and dissemination: This study is approved by the Swedish Ethical Review Board (reference number 2019–03347) in Gothenburg. We plan to disseminate the knowledge gained from this study by publishing our results in peer-reviewed scientific journals and other scholarly outlets. Trial registration number: NCT04128644; Pre-results .